Efficiency and residual effect of alternative potassium sources in grain crops - Soratto, Rogério Peres [UNESP]; Crusciol, Carlos Alexandre Costa [UNESP]; de Campos, Murilo [UNESP]; Gilabel, Amanda Prado [UNESP]; da Costa, Claudio Hideo Martins; Castro, Gustavo Spadotti Amaral; Neto, Jayme Ferrari (FapUNIFESP (SciELO), 2021)
The objective of this work was to evaluate the efficiency and the residual effects of both molten and ground alkaline potassium-silicate rocks (K1) and of ground phonolite rock (K2), as sources of potassium, compared with the traditional source (KCl), in grain crop successions. Two experiments – one with the succession soybean-wheat-corn and the other with the succession corn-millet-soybean – were conducted on a Typic Haplorthox in a randomized complete block design with four replicates. The treatments consisted of three sources (KCl, K1, and K2) and four rates of K (corresponding to 0, 0.5, 1.0, and 2.0 times the recommended rates for soybean and corn). The used sources did not affect leaf K concentration in soybean, but KCl and K2 similarly increased leaf K concentration in corn. Regardless of the source, K application increased the yield of all crops. The K1 and K2 sources present agronomic efficiencies equivalent to that of KCl. K1 and K2 show a more pronounced residual effect than KCl, especially on crops grown approximately one year after their application and under K rates above those recommended for the crops.
Eficiência e efeito residual de fontes alternativas de potássio em culturas graníferas
Keywords: Agronomic efficiency; Phonolite; Potassium fertilization; Residual effect; Rock dust; Silicon